Fully alloyed metal nanorods with highly tunable properties. Issue 8 (7th February 2017) - Albrecht, Wiebke; van der Hoeven, Jessi E. S.; Deng, Tian-Song; de Jongh, Petra E.; van Blaaderen, Alfons
Abstract : Fully alloyed anisotropic nanoparticles can be obtained with complete retention of the particle shape via thermal treatment allowing for tunable plasmonic properties. Abstract : Alloyed metal nanorods offer a unique combination of enhanced plasmonic and photothermal properties with a wide variety in optical and catalytic properties as a function of the alloy composition. Here, we show that fully alloyed anisotropic nanoparticles can be obtained with complete retention of the particle shape via thermal treatment at surprisingly low temperatures. By coating Au–Ag, Au–Pd and Au–Pt core–shell nanorods with a protective mesoporous silica shell the transformation of the rods to a more stable spherical shape was successfully prevented during alloying. For the Au–Ag core–shell NRs the chemical stability was drastically increased after alloying, and from Mie–Gans and finite-difference time-domain (FDTD) calculations it followed that alloyed AuAg rods also exhibit much better plasmonic properties than their spherical counterparts. Finally, the generality of our method is demonstrated by alloying Au–Pd and Au–Pt core–shell NRs, whereby the AuPd and AuPt alloyed NRs showed a surprisingly high increase in thermal stability of several hundred degrees compared with monometallic silica coated Au NRs.